Duchenne muscular dystrophy: recent insights in brain related comorbidities - Cyrille Vaillend; Yoshitsugu Aoki; Eugenio Mercuri; Jos Hendriksen; Konstantina Tetorou; Aurelie Goyenvalle; Francesco Muntoni (Nature Communications)
Abstract Duchenne muscular dystrophy (DMD), the most common childhood muscular dystrophy, arises from DMD gene mutations, affecting the production of muscle dystrophin protein. Brain dystrophin-gene products are also transcribed via internal promoters. Their deficiency contributes to comorbidities, including intellectual disability ( ~ 22% of patients), autism ( ~ 6%) and attention deficit disorders ( ~ 18%), representing a major unmet need for patients and families. Thus, improvement of their diagnosis and treatment is needed. Dystrophic mouse models exhibit similar phenotypes, where genetic therapies restoring brain dystrophins improve their behaviour. This suggests that future genetic therapies could address both muscle and brain dysfunction in DMD patients.